Callous-Unemotional Traits and the Treatment of Conduct Problems in Childhood and Adolescence: A Comprehensive Review - Hawes, David J.; Price, Matthew J.; Dadds, Mark R. (Clinical child and family psychology review, 2014)
The treatment of conduct problems among children and adolescents with callous-unemotional (CU) traits has been subject to much speculation; however, treatment outcome research has been surprisingly limited and findings have been mixed. This review examines the research to date in this field as it pertains to two key questions. First, are CU traits associated with clinical outcomes and processes in the family based treatment of child and adolescent conduct problems? Second, can family based intervention produce change in CU traits? Using a systematic search strategy, we identified 16 treatment outcomes studies that can be brought to bear on these questions. These studies provide strong evidence of unique associations between CU traits and risk for poor treatment outcomes, while at the same time indicating that social-learning-based parent training is capable of producing lasting improvement in CU traits, particularly when delivered early in childhood. We discuss the potential for this emerging evidence base to inform the planning and delivery of treatments for clinic-referred children with CU traits, and detail an ongoing program of translational research into the development of novel interventions for this high-risk subgroup.